Management perspectives from patients with fibromyalgia experiences with the healthcare pathway: a qualitative study - Kachaner, Alexandra; Harim, Magda; Combier, Alice; Trouvin, Anne Priscille; Avouac, Jérôme; Ranque, Brigitte; Piot, Marie-Aude (Frontiers in Medicine, 2023)
Background: Fibromyalgia is a prevalent condition affecting 1-2% of the general population and can result in significant disability. Physicians and patients frequently encounter challenges in managing this condition. Aim: To explore novel management approaches through a qualitative analysis of the doctor-patient relationship. Design and Setting: Telephone interviews were conducted with fibromyalgia patients to investigate their healthcare experiences. Methods: Qualitative analysis was performed on patients' narratives using Interpretative Phenomenological Analysis, a methodology that delves into each individual's subjectivity. Results: Nineteen adult patients with fibromyalgia, primarily middle-aged women (84% women, mean age 49.8 years), recruited from two university centers in Paris, were included in the study. The narratives of participants revealed substantial suffering and considerable functional impairment, which is paradoxical for a condition often considered benign. They reported an ongoing sense of loss of control, exacerbated by an imbalanced patient-doctor relationship. Patients constantly feared not being heard or believed and frequently sought attention from their caregivers. Most participants displayed significant ambivalence toward the nature of their condition and actively sought causal links. Patients' adaptive strategies sometimes worsened their symptoms, as in the case of muscular deconditioning. The healthcare system appeared deficient in managing these patients, characterized by a lack of health professional training, frequent inappropriate responses from healthcare providers, and stigmatization of psychological conditions. Conclusion: Despite its perceived benign nature, fibromyalgia should be regarded as a severe condition due to its substantial long-term consequences. Participants reported a challenging experience with the doctor-patient relationship, marked by a strong sense of dependence and a lack of recognition. The care pathway for these patients appeared unsuitable and disorderly, potentially resulting in iatrogenic consequences. Management of patients with fibromyalgia should be enhanced and directed toward a patient-centered approach. The study provides practical recommendations regarding communication methods and patient care.